Landscape configuration in seagrass meadows and its influence on carbon stock in reef lagoon systems - Herrera-Silveira, Jorge Alfredo; Palafox-Juárez, Erika Betzabeth; Mendoza-Martínez, Juan Enrique; Montero Muñoz, Jorge Luis; Teutli Hernández, Claudia (Frontiers in Marine Science, 2025)
Seagrass meadows play a crucial role due to their ability to store carbon, mitigate the effects of climate change, and provide important ecosystem services such as coastal protection and water quality improvement. It has been observed that their carbon storage capacity varies depending on factors such as leaf structure, substrate type, depth, hydrodynamics, and spatial configuration. To assess the relationship between the landscape configuration of seagrass meadows and carbon storage, ten reef lagoons from the northern and southern regions of the Veracruz Reef System National Park were analyzed. Vegetation and soil data were collected from 513 sampling sites, and biomass organic carbon (BOC) and soil organic carbon (SOC) samples were taken at 153 of these sites, down to a depth of 25 cm. Through a supervised classification of WorldView2 satellite imagery, landscape maps were generated, and their composition and configuration were analyzed using 13 landscape metrics. A Generalized Additive Model fitted to distance-based redundancy analysis, was then applied to identify the relationship between landscape configuration and carbon storage (SOC5cm). Three types of seagrass meadows were identified: low density on rock, medium density on sand and rock, and high density on sand. Significant differences were observed in both carbon concentration and landscape configuration. High-density meadows exhibited the highest carbon concentrations in both biomass and soil (SOC25cm), while low-density meadows on rock recorded the lowest concentrations. The results showed that in the northern region, landscapes were more fragmented and had lower carbon storage capacity, whereas in the southern region, more cohesive and connected seagrass meadows stored greater amounts of carbon. Landscape metrics such as mean patch size and aggregation index were correlated with SOC5cm variations in southern landscapes, while edge density was the most influential metric in the north. The findings indicated that more fragmented landscapes with higher edge density exhibited lower carbon storage capacity, likely due to greater exposure to erosive processes. In contrast, more connected and cohesive landscapes, particularly in regions less affected by human activities, retained larger amounts of carbon in both biomass and soil. These findings highlight the importance of landscape configuration in the carbon storage capacity of seagrass meadows and emphasize the need to conserve their structural integrity to maximize their potential as carbon sinks and other ecosystem services.